Barriers to essential surgical care experienced by women in the two northernmost regions of Ghana: a cross-sectional survey. Issue 1 (December 2016) - Gyedu, Adam; Abantanga, Francis; Boakye, Godfred; Gupta, Shailvi; Otupiri, Easmon; Agbeko, Anita; Kushner, Adam; Stewart, Barclay
Abstract Background Women in developing countries might experience certain barriers to care more frequently than men. We aimed to describe barriers to essential surgical care that women face in five communities in Ghana. Methods Questions regarding potential barriers were asked during surgical outreaches to five communities in the northernmost regions of Ghana. Responses were scored in three dimensions from 0 to 18 (i.e., 'acceptability, ' 'affordability, ' and 'accessibility'; 18 implied no barriers). A barrier to care index out of 10 was derived (10 implied no barriers). An open-ended question to elicit gender-specific barriers was also asked. Results Of the 320 participants approached, 315 responded (response rate 98 %); 149 were women (47 %). Women had a slightly lower barriers to surgical care index (median index 7.4; IQR 3.9–9.1) than men (7.9; IQR 3.9–9.4;p = 0.002). Compared with men, women had lower accessibility and acceptability dimension scores (14.4/18 vs 14.4/18;p = 0.001 and 13.5/18 vs 14/18;p = 0.05, respectively), but similar affordability scores (13.5/18 vs 13.5/18;p = 0.13). Factors contributing to low dimension scores among women included fear of anesthesia, lack of social support, and difficulty navigating healthcare, as well as lack of hospital privacy and confidentiality. Conclusion Women had a slightly lower barriers to surgical care index than men, which may indicate greater barriers to surgical care. However, the actual significance of this difference is not yet known. Community-level education regarding the safety and benefits of essential surgical care is needed. Additionally, healthcare facilities must ensure a private and confidential care environment. These interventions might ameliorate some barriers to essential surgical care for women in Ghana, as well as other LMICs more broadly.